The Role of Communications in Key National, Regional, Provincial and Local Government Development Initiatives - Stavrou, Aki (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2000)
This paper seeks to outline how the lack of a coherent communications input impacts on the implementation of local government development, by scanning existing legislation and seeking to draw upon the myriad of existing development strategies, in order to ascertain if, where and how communications have been incorporated into development strategies. The author examines a range of policy, legislation and implementation strategies central to the pursuit of development and growth which he demonstrates have neglected to incorporate communications as an element of development. He then explores possible strategies to incorporate communications within spatial planning and other implementation processes without which regions and provinces will not be able to pursue coherent, compatible, or even effective development policies.